Jaw‐retraction exercise increases anterior hyoid excursion during swallowing in older adults with mild dysphagia. (20th October 2021) - Hasegawa, Shohei; Nakagawa, Kazuharu; Yoshimi, Kanako; Yamaguchi, Kohei; Nakane, Ayako; Ishii, Miki; Okumura, Takuma; Hara, Koji; Minakuchi, Shunsuke; Tohara, Haruka
Abstract: Objectives: The present study aimed to evaluate the effectiveness of a newly designed jaw‐retraction exercise for strengthening the geniohyoid muscle and thus improving the anterior movement of the hyoid bone during swallowing. Background: Although previous studies suggest a relationship between anterior hyoid excursion and upper esophageal sphincter (UES) opening, there are currently no reports of physical exercises without the use of special equipment that can effectively improve this movement of the hyoid bone during swallowing. Materials and methods: This before‐after study included patients presenting to the authors' hospital with mild dysphagia (Level 5 on the Dysphagia Outcome and Severity Scale). The participants were instructed to perform a jaw‐retraction exercise designed to strengthen the geniohyoid muscle. Each participant was instructed to perform two sets of the exercise daily for four weeks, with each set consisting of five repetitions. Before and after the four‐week training period, videofluoroscopic swallowing studies were performed and later analysed. Results: Twenty‐five patients with a median age of 77 were included. The median peak anterior hyoid position before and after exercise were 129.82 and 132.74 (%C2‐C4 length), respectively, and this increase was found to be significant ( P  = .007). The median extent of UES opening before and after exercise were 8.6 and 9.3 (mm), respectively, and this increase was also found to be significant ( P  = .040). Conclusion: Our findings demonstrate that the jaw‐retraction exercise can effectively improve the anterior movement of the hyoid bone. This exercise may be effective in individuals with oral frailty when signs of swallowing disorders are observed.